(3CSFdI hCLhHIs - (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3SDGd de UGQ ef cGfJ cGf GdLgd Ydjg ZGdHkG LhGH dCf MSf GdNdb jJHY TOg Gdbhe ef GdfaS s
(3BNQgG (B:s
(3dGf GdfaS GPG JMQc JMQc eYg GdHOf hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GfXQ GdeNWhW Qbe (B259 (3bdjdg GdEYLGes
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI GdMbhb (B(112(3H(B) s
Keywords: (3GdadSaI hGdefWbs